2022
DOI: 10.1073/pnas.2210321119
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CHROMR regulates antiviral immunity in humans

Abstract: Long noncoding RNAs (lncRNAs) have emerged as critical regulators of gene expression, yet their contribution to immune regulation in humans remains poorly understood. Here, we report that the primate-specific lncRNA CHROMR is induced by influenza A virus and SARS-CoV-2 infection and coordinates the expression of interferon-stimulated genes (ISGs) that execute antiviral responses. CHROMR depletion in human macrophages reduces histone acetylation at regulatory regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Data sources (DEG data set: articles or data set identifier) are numbered and visually delimited by an alternance of light-gray/dark-gray backgrounds, with some sources providing several samples or time points ( supplementary table S10, Supplementary Material online). Samples sources are: (1) Alberts et al (2022) ; (2) Park et al (2022) ; (3) van Solingen et al (2022) ; (4) Chandrashekar et al (2021) ; (5) Chow et al (2021) ; (6) Blanco-Melo et al (2020) ; (7) Deshiere et al (2017) ; (8) Golumbeanu et al (2019) ; (9) van der Heijden et al (2021) ; (10) Bauby et al (2021) ; (11) GSE53993; (12) Coelho et al (2021) ; (13, 14) Devadas et al (2016) ; (15) Bell et al (2022) ; (16) GSE186908; (17) GSE192528; (18) Thompson et al (2020) ; (19, 63–65) Tsalik et al (2021) ; (20, 28, 62) Dissanayake et al (2020) ; . (21) Zhuravlev et al (2020) ; (22) GSE97672; (23, 27) GSE89008; (24) GSE82232; (25) GSE101760; (26) GSE97672; (29) Sheng et al (2020) ; (30) Hong et al (2021) ; (31) Mrozek-Gorska et al (2019) ; (32) Wang et al (2019) ; (33) Yanagi et al (2021) ; (34) GSE84897; (35) Tso et al (2018) ; (36) Journo et al (2018) ; (37) GSE79032; (38) Seelbinder et al (2020) ; (39) Oberstein and Shenk (2017) ; (40–42) Sen et al (2020) ; (43) Zhang et al (2016) ; (44, 49) Jagya et al (2014) ; (45) Yuan et al (2021) ; (46) GSE194179; (47) Zai et al (2022) ; (48) Winer et al (2020) ; (50) Montanari et al (2022) ; (51) Tegtmeyer et al (2021) ; (52) Hojka-Osinska et al (2017) ; (53) Li et al (2020) ; (54) GSE84346; (55) Hu et al (2016) ; (56, 59, 60) Kaczkowski et al (2012) ; (57)…”
Section: Resultsmentioning
confidence: 99%
“…Data sources (DEG data set: articles or data set identifier) are numbered and visually delimited by an alternance of light-gray/dark-gray backgrounds, with some sources providing several samples or time points ( supplementary table S10, Supplementary Material online). Samples sources are: (1) Alberts et al (2022) ; (2) Park et al (2022) ; (3) van Solingen et al (2022) ; (4) Chandrashekar et al (2021) ; (5) Chow et al (2021) ; (6) Blanco-Melo et al (2020) ; (7) Deshiere et al (2017) ; (8) Golumbeanu et al (2019) ; (9) van der Heijden et al (2021) ; (10) Bauby et al (2021) ; (11) GSE53993; (12) Coelho et al (2021) ; (13, 14) Devadas et al (2016) ; (15) Bell et al (2022) ; (16) GSE186908; (17) GSE192528; (18) Thompson et al (2020) ; (19, 63–65) Tsalik et al (2021) ; (20, 28, 62) Dissanayake et al (2020) ; . (21) Zhuravlev et al (2020) ; (22) GSE97672; (23, 27) GSE89008; (24) GSE82232; (25) GSE101760; (26) GSE97672; (29) Sheng et al (2020) ; (30) Hong et al (2021) ; (31) Mrozek-Gorska et al (2019) ; (32) Wang et al (2019) ; (33) Yanagi et al (2021) ; (34) GSE84897; (35) Tso et al (2018) ; (36) Journo et al (2018) ; (37) GSE79032; (38) Seelbinder et al (2020) ; (39) Oberstein and Shenk (2017) ; (40–42) Sen et al (2020) ; (43) Zhang et al (2016) ; (44, 49) Jagya et al (2014) ; (45) Yuan et al (2021) ; (46) GSE194179; (47) Zai et al (2022) ; (48) Winer et al (2020) ; (50) Montanari et al (2022) ; (51) Tegtmeyer et al (2021) ; (52) Hojka-Osinska et al (2017) ; (53) Li et al (2020) ; (54) GSE84346; (55) Hu et al (2016) ; (56, 59, 60) Kaczkowski et al (2012) ; (57)…”
Section: Resultsmentioning
confidence: 99%
“…Though it could be expected that lncRNA overlapping sense mRNA would modulate the levels of overlapped gene mRNA, such an effect could not be observed regarding lncRNA CHROMR and protein coding PRKRA . Indeed, it has been shown that CHROMR shows a weak interaction with the PRKRA genomic locus and that CHROMR expression does not impact the expression of the PRKRA gene ( van Solingen et al, 2022 ) at least in the context of macrophages. However, lncRNA are known for their ability to modulate gene activity without impacting levels of mRNA, so it is not yet conclusive that CHROMR does not interact with PRKRA .…”
Section: Discussionmentioning
confidence: 99%
“…However, lncRNA are known for their ability to modulate gene activity without impacting levels of mRNA, so it is not yet conclusive that CHROMR does not interact with PRKRA . Interestingly, CHROMR has been shown to have histone binding affinity in macrophages ( van Solingen et al, 2022 ), which could still be an avenue for PRKRA regulation, without binding to PRKRA mRNA. It is also known that CHROMR can act as a sponge for various miRNAs ( Hennessy et al, 2019 ; Wang et al, 2022 ), but it would be difficult to attribute miRNA sponging to observed effects on glioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations